Revascularisation in older adult patients with non-ST-segment elevation acute coronary syndrome: effect and impact on 6-month mortality. Issue 4 (1st June 2020) - Bardaji, Alfredo; Barrabés, José A; Ribera, Aida; Bueno, Héctor; Fernández-Ortiz, Antonio; Marrugat, Jaume; Oristrell, Gerard; Ferreira-González, Ignacio
Abstract: Although revascularisation in non-ST-segment elevation acute coronary syndrome (NSTEACS) is associated with better outcomes, its impact in older adult patients is unclear. This is a retrospective analyses of three national NSTEACS registries conducted during the past decade in Spain. Patients aged 75 years and older were included: DESCARTES (DES; year 2002; n =534), MASCARA (MAS; 2005; n =1736) and DIOCLES (DIO; 2012; n =593). The adjusted association between revascularisation and total (inhospital and 6-month) mortality was estimated by two-stage meta-analysis (pooled effect across the three registries with inverse-variability weights) and one-stage meta-analysis (multilevel model with random effects across studies). The impact of revascularisation was assessed comparing the observed and the expected mortality based on a logistic regression model in the pooled database. Although revascularisation was associated with a lower risk of mortality in meta-analyses (two-stage: odds ratio 0.44, 95% confidence interval 0.29–0.67; one-stage: odds ratio 0.54, 95% confidence interval 0.36–0.81) and the revascularisation rate increased steadily from 2002 (DES 14.2%) to 2012 (DIO 43.7%), its impact was not patent across registries, probably because this increase was concentrated in low and medium-risk GRACE strata (tertile 1, 2 and 3: MAS 59%, 20% and 6%; DIO 64%, 39% and 19%, respectively). In conclusion, a consistent increase of revascularisation in NSTEACS in older adults was not followed by a decrease in mortality at 6 months, probably because the impact of this strategy is limited to the higher risk population, the stratum with the lowest revascularisation rate in real life.